Blood Group Identification using FPGA (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Detection of Blood Group is the first essential proce- dure for major medical surgery. Traditional ways of laboratorytesting techniques like plate test and tube test are susceptible to human fallibility and, the approach of detecting blood groupsis still prevalent in our modern era of digitization. As it is time-consuming, the results are difficult to reproduce, and there is aneed for a domain expert. Our present times necessitate automation of the evaluation process. This approach would be alifesaving method for Blood Group Identification.The proposed system uses a technique of testing using FPGA. Canny Edge Detection Algorithm developed using MATLABSimulink and converted to HDL Code for Hardware Implemen- tation on Arty 7000 Zync FPGA using Xilinx Vivado softwareas FPGAs have the advantages of speed and reconfigurability for image processing applications. The Detected edges countedto classify blood group. The proposed Hardware Model FPGA demonstrates 2.5 V power supply with the power usage of 1.83W. Its Hardware implementation requires only 10.773ns, while Intel Core i5 processor with 1.60 GHz clock rate and 8 GBRAM takes 120 s upon software-based MATLAB implementation. An accuracy of 99% achieved when tested with each typeof blood with more than 100 various blood samples produced advantages like portable, affordable, durable, and more limitedpower consumption than conventional methods of detecting blood group by the proposed hardware solution.